Автоматизированная система разработки планов развития производства - Суслов О. П. Олег Павлович; Арабаджев А. М. Александр Мартынович; Гирник Л. П. Людмила Петровна; Дроздова Л. М. Людмила Михайловна (Киев, Технiка, 1984)
Авт. указаны на обороте тит. л.